The Analytical Descriptive Study of the Effect of Drinking Water Contamination on the Spread of Hepatitis A Virus in DARAA Governorate-Syria - Alhommada , Wisal; Alkrad , Tameem; Alkrad, khaldon (Scientific Journal of University of Benghazi, 2024)
This study aimed to find out the effect of drinking water pollution on the spread of hepatitis A virus in “Al-Sabil neighborhood” in Daraa governorate in Syria and to know the infection rate in terms of sex (male, female), and age according to age groups (0-12, 13-18, 19-40, 41-60, over 60). Also according to the onset of symptoms (0-10, 11-20 and 21-30) days, and according to the recovery period (less than 100 days - more than 100 days). The results of the analysis showed that the number of doubtful cases was (6526), ​​where the positive cases were (2118) and the negative cases (4408), As it was shown that males were infected more than females, and the age group from (19-40)year was more susceptible to infection compared to the rest of the age groups, and symptoms began to appear during the first ten days of infection, with a rate of 59.73%, followed by the period from (21-30) days with a rate of 27%, and recovery occurred after one hundred days of infection, at a rate of 59.96%, and it was a significant correlation between the infection and the age, also between one set symptoms and Duration of recovery.